GonePhishing
New member
- Joined
- Nov 1, 2016
- Messages
- 2
Given:
So I've found:
I thougt at this point, I could then do f(h) or f(x-a) by substituting x=h or x=x-a, but the answer is expected to be only in terms of h, so I am not sure what to do next.
Any help would be much appreciated
f(x)=(a/x)12-2(a/x)6
Use a Taylor Expansion about x=a to obtain an approximate expression for f(h), where h=x-a, to a second order in h.
So I've found:
f'(x)=12a6/x7-12a12/x13
f''(x)=156a12/x14-84a6/x8
And evaluated at x=a:f''(x)=156a12/x14-84a6/x8
f(a)=-1
f'(a)=0
f''(a)=72/a2
This gives the expansion:f'(a)=0
f''(a)=72/a2
f(x)=36(x-a)2/a2-1
I thougt at this point, I could then do f(h) or f(x-a) by substituting x=h or x=x-a, but the answer is expected to be only in terms of h, so I am not sure what to do next.
Any help would be much appreciated